2017
DOI: 10.1371/journal.pone.0180148
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport protein 1 regulates retinoid metabolism and photoreceptor development in mouse retina

Abstract: In retinal pigment epithelium (RPE), RPE65 catalyzes the isomerization of all-trans-retinyl fatty acid esters to 11-cis-retinol in the visual cycle and controls the rhodopsin regeneration rate. However, the mechanisms by which these processes are regulated are still unclear. Fatty Acid Transport Protein 1 (FATP1) is involved in fatty acid uptake and lipid metabolism in a variety of cell types. FATP1 co-localizes with RPE65 in RPE and inhibits its isomerase activity in vitro. Here, we further investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…Similarly, pan-retinal or dRPC-specific expression of dFatp caused a loss of dRPCs of about 10%, resulting in perturbation of the organization of ommatidia in Drosophila retina (Fig 6E and 6F). In contrast to the dRPCs, photoreceptor cell survival (visualized by expression of Rh1-GFP) was unaffected by dFatp overexpression in dRPCs (Fig 6G, left panels, and 6H), which is in agreement with our previous findings in the mouse [30]. Therefore, Fatp -mediated LD accumulation in RPCs does not appear to be deleterious to photoreceptor cells under normal physiological conditions.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, pan-retinal or dRPC-specific expression of dFatp caused a loss of dRPCs of about 10%, resulting in perturbation of the organization of ommatidia in Drosophila retina (Fig 6E and 6F). In contrast to the dRPCs, photoreceptor cell survival (visualized by expression of Rh1-GFP) was unaffected by dFatp overexpression in dRPCs (Fig 6G, left panels, and 6H), which is in agreement with our previous findings in the mouse [30]. Therefore, Fatp -mediated LD accumulation in RPCs does not appear to be deleterious to photoreceptor cells under normal physiological conditions.…”
Section: Resultssupporting
confidence: 91%
“…We found that LD accumulation in RPCs induced by ectopic expression of FATP is not toxic to photoreceptors in either Drosophila (this study) or mice [30], suggesting that LDs are not deleterious under normal physiological conditions. In addition to acting as an energy source, LDs may also reduce the cellular sensitivity to ROS.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations